Nonalcoholic Steatohepatitis Is the Fastest Growing Cause of Hepatocellular Carcinoma in Liver Transplant Candidates - Younossi, Zobair; Stepanova, Maria; Ong, Janus P; Jacobson, Ira M; Bugianesi, Elisabetta; Duseja, Ajay; Eguchi, Yuichiro; Wong, Vincent W; Negro, Francesco; Yilmaz, Yusuf; Romero-Gomez, Manuel; George, Jacob; et al. (Clinical gastroenterology and hepatology, 2019)
Although hepatitis B and C have been the main drivers of hepatocellular carcinoma (HCC), nonalcoholic steatohepatitis (NASH) has recently become an important cause of HCC. The aim of this study was to assess the causes of HCC among liver transplant (LT) candidates in the United States. The Scientific Registry of Transplant Recipients (2002-2016) was used to estimate the trends in prevalence of HCC in LT candidates with the most common types of chronic liver disease: alcoholic liver disease (ALD), chronic hepatitis B (CHB), chronic hepatitis C, and NASH. 158,347 adult LT candidates were included. Of these, 26,121 (16.5%) had HCC; this proportion increased from 6.4% (2002) to 23.0% (2016) (trend P < .0001). Over the study period, CHC remained the most common etiology for HCC (65%). The proportions of HCC accounted for by CHC and ALD remained stable (both trend P > .10), the proportion of CHB decreased 3.1-fold (P < .0001), while the proportion of NASH in HCC increased 7.7-fold (from 2.1% to 16.2%; P < .0001). Furthermore, since 2002, the prevalence of HCC in LT candidates with NASH increased 11.8-fold, while this rate increased 6.0-fold in CHB, 3.4-fold in ALD, and 2.3-fold in CHC (all P < .0001); the increasing trend in NASH was steeper than that for any other etiology (P < .0001 in a trend regression model). The proportion of LT candidates with HCC who ultimately received a transplant or died while waiting did not differ between etiologies (P > .05). Nonalcoholic steatohepatitis is the most rapidly growing cause of HCC among US patients listed for liver transplantation.